Gejala Klinis Neurologis dan Gambaran CT Scan Otak Pasien Kanker Paru Karsinoma Bukan Sel Kecil Metastasis ke Otak di Rumah Sakit Persahabatan - DIAN YULIANTI; ELISNA SYAHRUDDIN; AHMAD HUDOYO; AZIZA ICKSAN (Indonesian Journal of Cancer)
Brain is one of the common sites of distant metastasis in patients of lung cancer, and incidens of brain metastasis in lung cancer is considered high. In Non-small Cell lung cancer guide line, brain CT done if the neurological symptom occured. Therefore analysis of diagnostic approach related to brain metastases is needed.